HIGH QUALITY FINANCIAL REPORTING IN THE FUNCTION OF COMPANY GROWTH IN SERBIA - Ćeha, Nikola; Aničić, Jugoslav; Aničić, Dušan; Ćeha, Milenko; Nestorović, Olgica (The European Journal of Applied Economics, 2023)
Accounting profession and financial reporting quality development is moving alongside market economy development, which contributes to financial system stability and increases capital market efficiency as well as the efficiency of the entire economy. The investors opt for the markets they know well, and they have more confidence in the countries that have adopted and applied the international standards for financial reports. Therefore, the concern of all countries is to take active part in financial reporting international standards harmonization process in order to enable growth and increase in competitiveness of their companies in the international market. The first part of this paper indicates the importance and role of high quality financial reporting in modern situations. The second part of the paper presents the current situation of the financial reporting in the Republic of Serbia, while the third part contains the results of the research on the influence of various factors on the financial reporting quality in Serbia, with the suggestions for advance in the process and financial reporting quality improvement.
Keywords: financial reporting, international standards, company, Serbia